2002
DOI: 10.1530/eje.0.1460027
|View full text |Cite
|
Sign up to set email alerts
|

Clonal origin of non-medullary thyroid tumours assessed by non-random X-chromosome inactivation

Abstract: Objective: X-chromosome inactivation analysis was performed in order to assess the clonal origin of non-medullary thyroid tumours and to distinguish between multicentricity and multifocality in multiple papillary thyroid carcinoma (PTC). Methods: One hundred and thirteen tumour samples from 31 patients with isolated PTC, 16 patients with multinodular PTC, 14 patients with follicular thyroid adenoma (FTA) and 15 patients with follicular thyroid carcinoma (FTC) were collected. The corresponding normal thyroid ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 25 publications
2
29
0
Order By: Relevance
“…To account for possible differences in fluorescence signal acquisition and gel loading of each allele, we modified to uniform the volume of internal size marker (Genescan-500Liz; ABI Perkin Elmer, Warrington, United Kingdom) and calculated a corrected allele ratio as follows: (peak 1 height of undigested sample ÷ peak 2 height of undigested sample ÷ Liz 200 bp height of undigested group)/(peak 1 height of digested sample ÷ peak 2 height of digested sample ÷ Liz 200 bp height of digested group). We defined tumor samples as nonrandom XCI if this corrected ratio was less than 0.5 or greater than 2 [27]. Tumors were considered to be of single clonal origin if the same inactivation pattern was detected in each separate tumor from individual patient.…”
Section: Discussionmentioning
confidence: 99%
“…To account for possible differences in fluorescence signal acquisition and gel loading of each allele, we modified to uniform the volume of internal size marker (Genescan-500Liz; ABI Perkin Elmer, Warrington, United Kingdom) and calculated a corrected allele ratio as follows: (peak 1 height of undigested sample ÷ peak 2 height of undigested sample ÷ Liz 200 bp height of undigested group)/(peak 1 height of digested sample ÷ peak 2 height of digested sample ÷ Liz 200 bp height of digested group). We defined tumor samples as nonrandom XCI if this corrected ratio was less than 0.5 or greater than 2 [27]. Tumors were considered to be of single clonal origin if the same inactivation pattern was detected in each separate tumor from individual patient.…”
Section: Discussionmentioning
confidence: 99%
“…Both hypotheses, as presented by Kuhn et al [39], were confirmed in several studies. Despite the differences in molecular techniques among these studies, the common conclusion was that PTC multiplicity could be a result of either multicentricity or intrathyroidal spread [40-42]. One particularly interesting finding was that the ipsilateral PTC foci showed the same X chromosome inactivation pattern, and discordance was observed between contralateral nodules [39].…”
Section: Phenotypic and Molecular Heterogeneity Of Tc Subtypesmentioning
confidence: 99%
“…Furthermore, PTCs display microsatellite stability [56]. Taking these facts together with the tendency of PTC to occur as multicentric neoplasms, which are clonally independent from each other [37,54], it is tempting to advance that PTC tumorigenesis reflects the end product of (very) few oncogenic steps.…”
Section: Papillary Carcinomamentioning
confidence: 99%